Analysis of tree communities’ characterization in a seasonally dry forest for guiding forest management decision in South Benin, West Africa - GANGLO, COSSI JEAN; KINGBO, Armand; BABATOUNDE, Ghislain (My University, 2023)
Sustainable management of forest resources requires technical information’s for deci-sion-making. This study aimed to characterize tree communities in the forest of Dogo-Kétou wide of 42.850 ha in South Benin in order to reveal the silvicultural problems, which can contribute to its sustainable management. A forest inventory was achieved with fifty plots of 1 ha each installed and 250 quadrats of 100 m² each were used to study the forest’ regeneration. Different dendrometrical parameters were calculated. The di-ameter structures, the factorial correspondence analysis followed by the ascending hier-archical classification were also carried out with the software Ri386 3.5.3. The results revealed three tree communities with the densities varying between 23 and 26 trees/ha. The Shannon index of each tree community varies between 2.80 and 3.58 bits. Anogeissus leiocarpa, Daniellia oliveri and Vitellaria paradoxa’ community is the most diversified with an overall specific richness of 34 species and the high Shannon index obtained. The biotope of this tree community is the most productive of the forest. Despite the low floristic indices, this forest is exposed to strong anthropogenic pressures, which prevent the establishment of a mature dense forest. The analysis of the diameter structures reveals that the forest show the lack of big trees with dimeter superior than 45 cm, which are both mature and seed trees able of ensuring good regeneration for the future. The biological diversity of this forest is therefore threatened and deserves to be restored through strong sustainable management actions such as assisted regeneration, enrichment with commercial value species, strengthening the surveillance to prevent il-legal exploitation and promoting participatory management.
Keywords: Forest; inventory; sustainable management; decision-making; Benin.